The Influence of Financial Performance and Inflation on Firm Value in Indonesian Retail Companies - Salsabila Septia; Eka Yulianti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The retail subsector companies play a key role in economic growth, and their firm value is influenced by financial performance indicators such as liquidity, which can attract investors and signal company strength. This study examines the influence of financial performance and inflation on firm value in retail sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sample was selected using purposive sampling, resulting in 28 companies with 140 observations. Financial performance in this study is proxied by the current ratio and return on assets, while firm value is measured using price to book value. The analytical method used is multiple linear regression with SPSS version 27. The results show that the current ratio has a negative and significant effect on firm value, while return on assets has a positive and significant effect on firm value. Inflation, however, has no significant effect on firm value. All independent variables simultaneously have a significant effect on firm value. These findings indicate that internal financial performance plays a more dominant role in shaping retail firms’ value compared to macroeconomic conditions such as inflation.